HBV activates hepatic stellate cells through RUNX2/ITGBL1 axis - Fengchun Shi; Wei Tan; Wei Huang; Fei Ye; Mingjie Wang; Yongxiang Wang; Xinxin Zhang; Demin Yu (Virology Journal)
Abstract Background Chronic hepatitis B (CHB) remains a global health challenge, with liver fibrosis serving as a critical determinant of disease progression. Despite antiviral treatments, liver fibrosis often persists in CHB patients, highlighting the need for additional biomarkers and therapeutic targets. This study investigates the molecular mechanism underlying HBV-induced liver fibrosis, focusing on the role of RUNX2 in regulating integrin beta-like 1 (ITGBL1), a key factor in fibrogenesis. Methods We examined the relationship between RUNX2 and ITGBL1 in both in vitro hepatocyte models and an in vivo HBV mouse model. Using chromatin immunoprecipitation (ChIP), luciferase reporter assays, and Western blotting, we assessed RUNX2 binding to the ITGBL1 promoter and its impact on gene expression. We also evaluated the effects of RUNX2 inhibition using Vitamin D3 and CADD522 on ITGBL1 expression and hepatic stellate cell activation. Results Our findings reveal that RUNX2 directly binds to the ITGBL1 promoter, enhancing its expression and promoting hepatic stellate cell activation. We show that HBV infection significantly upregulates both RUNX2 and ITGBL1 in liver cells. Inhibition of RUNX2 with Vitamin D3 or CADD522 significantly reduced ITGBL1 levels and blocked hepatic stellate cell activation. These results suggest that the RUNX2/ITGBL1 pathway is critical in the progression of liver fibrosis in HBV-infected patients. Conclusions RUNX2 promotes liver fibrosis in HBV-infected patients by upregulating ITGBL1 expression. Our findings suggest that targeting RUNX2 could be a potential therapeutic approach to mitigate liver fibrosis in chronic hepatitis B.